Test Driven Ajax (on Rails) - Plumlee, Philip C. (O'Reilly short cut., 2007)
The World Wide Web has come a long way from static HTML pages. Today's developers enforce and enjoy standards, and we have built the web's primitive tools into advanced libraries, frameworks, and platforms. With these new freedoms come new responsibilities. Developers can now write some amazing bugs. A bug in a web page, hosted in a free web browser, can render expensive servers useless. Modern editors help rapidly write tangled and crufty code, the perfect habitat for bugs of every species, in situations that are hard to debug. We need help from the mortal enemy of the bug: Test-First Programming. This Short Cut seeks fixes for the hardest situation in web development; proactive test cases for Ajax code. We survey existing techniques, and invent new ones. Our goal is heads-down programming, without repeatedly clicking on a web browser.